Against Money Laundering! Law Enforcement Against Illegal Transactions in the Capital Market - Sukamto, Bambang; Mintarsih, Mimin; Nurlilah, Widya (Reformasi Hukum, 2024)
The capital market is a means to accommodate and channel funds to the public and support business development which will support the growth of the economy as a whole. Money laundering often involves illegal transactions that use the capital market as a means to disguise the origin of funds derived from illegal activities. This research aims to analyse law enforcement efforts against money laundering in the capital market. The research method used is normative law and descriptive analysis. The results showed that the mode of money laundering in the capital market is still rampant because it does not recognise cross-border so it is freer so that the need for participation from various parties to fight and eradicate it. Law enforcement in combating money laundering in the capital market has not been effective because the legal apparatus still uses conventional methods in handling it. It can be concluded that there are still some challenges in combating money laundering in the capital market, such as legal loopholes and limited human resources and technology. As a recommendation, it is necessary to increase inter-agency cooperation, increase the capacity of law enforcement officials, and strengthen regulations and supervision to strengthen efforts to fight money laundering in the capital market.